Balanced Scorecard Development Using Nine Steps to Success™ at RSUD Jampangkulon - Rohmat Firmansyah; Desy Anisya Farmaciawaty (Eduvest - Journal of Universal Studies, 2026)
This study seeks to develop a more workable and structured strategic performance framework for RSUD Jampangkulon by applying the Balanced Scorecard and using the Nine Steps to Success as an implementation path. This study seeks to develop a more workable and structured strategic performance framework for RSUD Jampangkulon by applying the Balanced Scorecard and using the Nine Steps to Success as an implementation path. The research follows an analytical case study approach. An initial screening phase is used to identify a small set of performance framework options through a structured literature-based shortlist, then Value Focused Thinking is applied to decide which option fits the hospital needs most closely. The main phase develops the scorecard in a full sequence, starting from a program launch to set working boundaries, followed by situation assessment, strategy formulation, objective setting, strategy mapping, selection of a lean set of core KPIs from an existing indicator bank, design of linked strategic initiatives, preparation of monitoring and performance analysis routines, tier based alignment through cascading with role clarity, and the definition of an evaluation and refresh cycle. The findings suggest that dispersed mandated indicators can be reshaped into a manageable core scorecard that supports routine control, supported by a strategy map treated as a working hypothesis, more stable KPI definitions, an initiative portfolio tied to measures, and a review rhythm that encourages follow up actions.